2005
DOI: 10.1037/0033-2909.131.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Intelligence: The Same or Different Constructs?

Abstract: Several investigators have claimed over the past decade that working memory (WM) and general intelligence (g) are identical, or nearly identical, constructs, from an individual-differences perspective. Although memory measures are commonly included in intelligence tests, and memory abilities are included in theories of intelligence, the identity between WM and intelligence has not been evaluated comprehensively. The authors conducted a meta-analysis of 86 samples that relate WM to intelligence. The average cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
674
7
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 853 publications
(778 citation statements)
references
References 156 publications
58
674
7
22
Order By: Relevance
“…Furthermore, correlations between a WM composite and score on the Raven's Advanced Progressive Matrices test, which is often considered a prototypical Gf test, were .69, .59, and .61 in three studies reported in Salthouse (1993a Engle, Tuholski, Laughlin and Conway (1999), Kane, Hambrick, Tuholski, Wilhelm, Payne and Engle (2004), and Unsworth, Heitz, Schrock and Engle (2005). After adjusting for unreliability, Ackerman, Beier and Boyle (2004) found a meta-analytic estimate for the Gf-WM correlation of .63. The Gf-WM correlations are generally higher when the relations are examined at the level of factor scores, composite scores, or latent variables.…”
Section: Results Inmentioning
confidence: 91%
“…Furthermore, correlations between a WM composite and score on the Raven's Advanced Progressive Matrices test, which is often considered a prototypical Gf test, were .69, .59, and .61 in three studies reported in Salthouse (1993a Engle, Tuholski, Laughlin and Conway (1999), Kane, Hambrick, Tuholski, Wilhelm, Payne and Engle (2004), and Unsworth, Heitz, Schrock and Engle (2005). After adjusting for unreliability, Ackerman, Beier and Boyle (2004) found a meta-analytic estimate for the Gf-WM correlation of .63. The Gf-WM correlations are generally higher when the relations are examined at the level of factor scores, composite scores, or latent variables.…”
Section: Results Inmentioning
confidence: 91%
“…Once a group-level based connectivity model is available, the method enables to classify new subjects on the basis of their individual connectivity profile. Second, we cannot exclude that the present metabolic and structural relationships with verbal WM are not driven by more global cognitive characteristics such as general intelligence (Ackerman et al, 2005). …”
Section: Discussionmentioning
confidence: 91%
“…This finding indicates that group differences in WM may be attributable to differences in general intelligence. Relationships between WM capacity and intellectual ability have also been documented by studies of typically -19 -developing children and young adults (Ackerman, Beier, & Boyle, 2005;Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013).…”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 99%